Rancang Bangun Aplikasi Modul Pembelajaran Satwa Untuk Anak Berbasis Mobile Augmented Reality - Kholid Fathoni; Yuliana Setiowati; Rozy Muhammad (JURNAL MEDIA INFORMATIKA BUDIDARMA, 2020)
Education in children is a very important part of life to achieve success in the future. Early on, children must be taught knowledge, especially related to the daily environment, including: introduction of animals. Among the characteristics of children's learning is interesting. So far, conventional learning in the form of books makes children bored, so it takes creativity or interactive learning methods, one of which is multimedia-based learning. One of the multimedia technology developed at this time is augmented reality. Mobile augmented reality based applications can be used as learning media for animal recognition for children. This interactive learning media based on Mobile Augmented Reality, called ARnimal, combines picture books and augmented reality applications. The markers contained in the picture book will be captured by the camera from the mobile device and then processed and appear animated 3D animals on the screen in realtime. By combining the real and virtual world, ARnimal can stimulate the imagination of children so that children are more enthusiastic in learning. The results of this ARnimal trial on several types of smartphones show that all ARnimal functions are running well. ARnimal was also tested on some children who were accompanied by their parents and the results of the questionnaire showed that the application was easy to use, helped with education, had similarities with real animals and had an attractive appearance.